Kesenjangan Mutu Pendidikan Tinggi di Indonesia: Analisis Ketimpangan Sumber Daya, Tata Kelola, dan Daya Saing Perguruan Tinggi - Wirdatul Aini; Aqimi Dinana (Regalia Institute, 2025)
Higher education or higher education in Indonesia basically still needs to improve. When compared to higher education abroad, in Indonesia there are still many problems that need attention. Not only that, these problems should also have solutions so that higher education in Indonesia can be more advanced in the future. There are several problems that make higher education in Indonesia must be improved. Gaps occur when there is a distance between reality and expectations. Universities are competing to build a curriculum that is able to answer the challenges of the world of work, so that graduates can quickly be absorbed in the world of work after graduating from education and the gap can be minimized.